2015
DOI: 10.1021/acs.jpcc.5b08813
|View full text |Cite
|
Sign up to set email alerts
|

Growing Inorganic Membranes in Microfluidic Devices: Chemical Gardens Reduced to Linear Walls

Abstract: The hollow precipitate tubes in chemical gardens conserve the nonequilibrium conditions present during their formation and are an important example of molecular processes causing complex macroscopic self-organization. We report a greatly simplified experimental model of these structures that is based on the formation of an inorganic membrane in a microfluidic device. Within this device, we induce the precipitation of Mn­(OH)2 and other metal hydroxides at the reactive interface of steadily injected NaOH and Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 64 publications
7
88
0
Order By: Relevance
“…In addition, the wall thickening occurs strictly in the direction of slightly acidic, metal salt solution and not toward the alkaline silicate solution. Whereas this observation was originally made for silicate systems, the results from microfluidic growth experiments confirmed this finding for precipitation reactions between sodium hydroxide and various metal salt solutions including magnesium, manganese, iron, cobalt, and copper (28). Here we present experimental measurements on the growth of precipitate membranes in a microfluidic system together with an analytical model that captures key aspects of the growth dynamics.…”
Section: Significancesupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the wall thickening occurs strictly in the direction of slightly acidic, metal salt solution and not toward the alkaline silicate solution. Whereas this observation was originally made for silicate systems, the results from microfluidic growth experiments confirmed this finding for precipitation reactions between sodium hydroxide and various metal salt solutions including magnesium, manganese, iron, cobalt, and copper (28). Here we present experimental measurements on the growth of precipitate membranes in a microfluidic system together with an analytical model that captures key aspects of the growth dynamics.…”
Section: Significancesupporting
confidence: 69%
“…Furthermore, one can reduce the dimensionality of the system by the injection of salt solutions from a point-like source into a thin, horizontal layer of silicate solution contained within a Hele-Shaw cell (25)(26)(27). This approach was taken further by studying the formation of precipitate membranes in a microfluidic device at the planar interface between two parallel, cocurrent reactive fluid streams (28). The…”
mentioning
confidence: 99%
“…The membrane initially formed at the reactive solution interface and thickened overtime in both directions while staying close to the middle of the serpentine‐shaped channel (see Movie S1 in the Supporting Information). As we can see from the micrograph in Figure b, the iron phosphate membrane was porous and heterogeneous and hence differed from the metal hydroxide membranes in our earlier studies . In previous studies the membranes showed no voids, acted as semi‐permeable membranes, and thickened only in the direction of the acidic metal salt solutions.…”
Section: Resultsmentioning
confidence: 58%
“…The polystyrene sheet was cut to the desired shape with an inexpensive electronic cutting tool (Silhouette Portrait) connected to a personal computer. The serpentine‐shaped channel started with a Y‐shaped pattern and had several semicircular‐ring segments connecting the other straight parts. The mixing part of the channel is 30 cm long, 3 mm wide, and approximately 200 μm high.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation